Pemberdayaan Masyarakat Desa Karang Sidemen Melalui Pemanfaatan Limbah Ternak Urin Sapi sebagai Pupuk Organik Cair - Nuraini, Zun; Ansar, Muhammad Asshiddiq; Perdana, Ansor; Kurniawan, Nanda Hardi; Erlinka, Rewika Budy; Wati, Safira Fathurrahma; Sumarsono, Joko (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
Karang Sidemen Village is an area with a majority population that relies on the agricultural and livestock sectors. However, livestock waste, especially cow urine, is often not utilized properly and has the potential to pollute the environment. This community service program aims to increase public knowledge and awareness in processing cow urine livestock waste into liquid organic fertilizer (POC) through a fermentation process, so that it can provide added economic value, reduce environmental pollution and support sustainable agriculture. This activity is carried out with a structured method in socialization activities starting from the participation of the Women Farmers Group (KWT) and the Ngiring Maju Farmers Group in Karang Sidemen Village. The processing process is carried out by collecting cow urine from the pen with an adequate drainage system, then fermented using EM4 as a starter. Fermentation is carried out for 14 days in an airtight container, followed by an aeration system to eliminate the smell of ammonia. The results of the activity show an increase in public understanding of livestock waste management and the ability to produce POC independently. The POC produced has a high nutrient content such as nitrogen, phosphorus, and potassium which are useful for binding soil fertility and increasing plant productivity. This activity not only reduces waste that pollutes the environment but also provides an alternative to chemical fertilizers that are more economical and environmentally friendly. In addition, this program provides added economic value to the community by opening up new business opportunities through the production and marketing of liquid organic fertilizers. With this activity, the community not only gains new skills, but is also encouraged to be more independent and productive in utilizing abundant local resources, while supporting sustainable village development.